Kemampuan Berfikir Kritis Siswa Kelas X SMA Negeri 1 Kartasura Tahun Pelajaran 2015/2016 Menggunakan Pembelajaran Inquiring Minds Want To Know Pada Pembelajaran Biologi - Hardianawati, Fitria; , Drs. Djumadi M.Kes (2016)
Nowadays, the innovation of active learning demands teachers to be more creative in teaching. This research aims to investigate the implementation of inquiring minds want to know learning strategy in Biology learning towards critical thinking abilities of the grade X students of SMA Negeri 1 Kartasura in the academic year of 2015/ 2016. According to educational field, this research is a quasy experiment by making a conclusion using a statistical analysis. The data collection techniques were written tests and interviews. The data analysis technique used data analysis using instrument testing and comparative testing techniques which obtained: (1) Essays for assessing critical thinking abilities were valid. It referred to the result of validity test identified that rtable was 0.355 and gained correlation score for 15 test items that was bigger than that of rtable, so the items were significantly correlated with the total score. (2) Essays for assessing critical thinking were reliable. It referred to the reliability test that Alpha was 0.885 and rtable was 0.355, so rtabel was 0.885 > 0.355. (3) Inquiring minds want to know learning influenced critical thinking abilities of the grade X students of SMA Negeri 1 Kartasura in the academic year of 2015/ 2016 in Biology subject. It referred to the mean scores of independent sample t test identified that probability score was 0.000, so the score was < 0.05